Pendidikan Karakter Prespektif Al-Quran Hadits - Anggi Fitri (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2018)
Character education is a systematically designed and executed effort to help learners understand the values ​​of human behavior related to God, self, fellow human beings, the environment, and nationality embodied in thoughts, attitudes, feelings, words and deeds based on religious norms, law, etiquette, culture, and customs. This paper aims to Understand the formulation of the concept of character education perspective Al Quran and Hadith. Through the understanding of textual and contextual understanding. The existing problems are answered through library research (library research). The data are collected from various references; both primary, secondary, and supporting data. Existing data were analyzed by hermeneutic approach by content analysis (content analysis). The results show that the Hadiths raised in this study contain human character or behavior towards God, self, fellow human being, and environment. Some concepts of character education that can be revealed from Al-Quran and Hadith is First, the foundation of character education, Second. The concept of character education in Islam. Third, the stages of character education formation. Fourth, the method of internalization character education. Fifth, the role of teachers and parents in character education.